2015
DOI: 10.1186/s12984-015-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combining robot-assisted therapy with neuromuscular electrical stimulation on motor impairment, motor and daily function, and quality of life in patients with chronic stroke: a double-blinded randomized controlled trial

Abstract: BackgroundRobot-assisted therapy (RT) is a widely used intervention approach to enhance motor recovery in patients after stroke, but its effects on functional improvement remained uncertain. Neuromuscular electrical stimulation (NMES) is one potential adjuvant intervention approach to RT that could directly activate the stimulated muscles and improve functional use of the paretic hand.MethodsThis was a randomized, double-blind, sham-controlled study. Thirty-nine individuals with chronic stroke were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 46 publications
(59 reference statements)
0
58
0
3
Order By: Relevance
“…Pure robot-assisted upper limb training also showed no superiority on motor improvements on chronic stroke in comparison with the traditional treatments in a reported randomized controlled trial ( 33 ). More recently, combined treatment with robot and NMES for the wrist by other research group also demonstrated more promising rehabilitation effectiveness in the upper limb motor recovery than pure robot training ( 34 ). However, most of the proposed devices are for single joint treatment, and the related trials were conducted on chronic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Pure robot-assisted upper limb training also showed no superiority on motor improvements on chronic stroke in comparison with the traditional treatments in a reported randomized controlled trial ( 33 ). More recently, combined treatment with robot and NMES for the wrist by other research group also demonstrated more promising rehabilitation effectiveness in the upper limb motor recovery than pure robot training ( 34 ). However, most of the proposed devices are for single joint treatment, and the related trials were conducted on chronic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the combined system can reduce the compensatory muscular activities at the elbow and can improve muscle activation levels related to the wrist in patients with chronic stroke, which was not observed when robot-assisted therapy was used alone ( 23 ). A study on the wrist training in patients with chronic stroke by another research group also demonstrated higher rehabilitation effectiveness in the upper-limb motor recovery with the combination therapy than with robot-assisted therapy alone ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the theory that interventions can be merged in order to enhance functional recovery [26], the combined use of FES and robotic technologies, referred to as Hybrid Robotic Rehabilitation Systems, has gained increased interest for arm stroke rehabilitation [27]. A recent RCT involving chronic stroke survivors showed that the combined action of robot-assisted therapy and FES for wrist movements in case of bimanual tasks has a positive effect on hand movement quality and spasticity [28]. More recently, a pilot RCT on 24 subacute stroke patients compared the training effects of an EMG-triggered FES-robotic system supporting elbow, wrist and finger movements with traditional physical therapy, showing that the novel system was more effective [29].…”
Section: Introductionmentioning
confidence: 94%